APPLICATION OF FIVE CHARACTER VALUES IN CHILDREN AGED 4-6 YEARS - . Kristianingsih (Magister Scientiae, 2019)
This study aims to describe: (1) the application of five character values in children aged 4-6 years and (2) the supporting and inhibiting factors for the application of five character values in children aged 4-6 years in Kanisius Kotabaru Kindergarten, Yogyakarta. This research is a qualitative research with a phenomenological approach. Data collection was done through observation, interviews, and documentation. The data were validated using an extension of participation, perseverance of observation and triangulation. The results of the study are (1) the application of five character values was done through: (a) systematic and procedural planning, (b) implementation that is integrated with each learning activity, and (c) evaluations which are carried out every day with a focus on three children, with the teacher giving report cards each semester as a result of one semester’s evaluation. (2) The supporting and inhibiting factors in implementing the five character values are as follows. (a) The support factors consist of exemplary teachers, teachers directly taking action against negative actions of children, parents participating in children's activities, and parents obeying the school rules. (b) The inhibiting factors in the application of five character values are: teachers who sometimes does not focus on the child when giving and replying to greetings, the teacher leaving the class during learning to meet guests, teachers who do not teach according to RPPH, parents who are too busy and parents who pay less attention to character education.